PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI DI SMA - Amanda Aulia; Romlah Romlah; Fitriani Fitriani (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The low interest and learning outcomes of students in Islamic Religious Education (PAI) at SMA Negeri 17 Bandar Lampung due to conventional teaching techniques are the background of this research. The focus of the problem is directed at the effectiveness of the Snowball Throwing model as an innovative solution to improve academic achievement. Using a quasi-experimental design with a non-equivalent control group approach, the research stages include administering a pretest, treatment, and posttest. The experimental group implemented Snowball Throwing, while the control group used Problem Based Learning. The test instrument used was proven valid and reliable with a Cronbach's Alpha value of 0.963. The results of quantitative analysis through the Mann-Whitney test showed a significant difference between the two groups with a significance value of p = 0.000 (p < 0.05). The data findings revealed that the average rank (mean rank) of the experimental class reached 32.73, far exceeding the control class which was only 17.67. This proves that the Snowball Throwing model significantly increases students' engagement, motivation, and cognitive understanding in the cognitive domains C2 and C3. The main conclusion of the study confirms that the use of Snowball Throwing is a highly effective and cutting-edge teaching strategy for optimizing Islamic Religious Education (PAI) learning outcomes in schools. Teachers are advised to adopt this active model to create a more dynamic, enjoyable, and inclusive learning ecosystem for all student learning styles in today's senior secondary education environment. ABSTRAK Rendahnya minat dan hasil belajar peserta didik pada mata pelajaran Pendidikan Agama Islam (PAI) di SMA Negeri 17 Bandar Lampung akibat teknik pengajaran konvensional menjadi latar belakang penelitian ini. Fokus masalah diarahkan pada efektivitas model Snowball Throwing sebagai solusi inovatif untuk meningkatkan prestasi akademik. Menggunakan desain kuasi-eksperimental dengan pendekatan non-equivalent control group, tahapan penelitian meliputi pemberian pretest, perlakuan, dan posttest. Kelompok eksperimen menerapkan Snowball Throwing, sementara kelompok kontrol menggunakan Problem Based Learning. Instrumen tes yang digunakan terbukti valid dan reliabel dengan nilai Cronbach's Alpha sebesar 0,963. Hasil analisis kuantitatif melalui uji Mann-Whitney menunjukkan perbedaan signifikan antara kedua kelompok dengan nilai signifikansi p = 0,000 (p < 0,05). Temuan data mengungkapkan peringkat rata-rata (mean rank) kelas eksperimen mencapai 32,73, jauh melampaui kelas kontrol yang hanya sebesar 17,67. Hal ini membuktikan bahwa model Snowball Throwing secara nyata meningkatkan keterlibatan, motivasi, dan pemahaman kognitif siswa pada ranah kognitif C2 serta C3. Simpulan utama penelitian menegaskan bahwa penggunaan Snowball Throwing merupakan strategi pengajaran yang sangat efektif dan mutakhir untuk mengoptimalkan hasil belajar PAI di sekolah. Guru disarankan mengadopsi model aktif ini guna menciptakan ekosistem pembelajaran yang lebih dinamis, menyenangkan, dan inklusif bagi seluruh gaya belajar siswa di lingkungan pendidikan menengah atas saat ini tuntas.